Boomerang art project. - Rautmann, Peter; Richter, Dorothee; Yamashita, Akiko; Kyoto Art Center, Kyoto; Künstlerhaus Bremen (Bremen : Gesellschaft für Aktuelle Kunst, 2001)
Bornemann, Hops ; Brandes, Urte ; Fichtner, Reinhard ; Garlichs, Burchhard ; Hinsch, Claudia ; Hirose, Midori ; Ishiyama, Yui ; Joost, Karsten ; Kawase, Karin ; Kuhn, Jürgen ; Lehmann, Marion ; Matsuo, Haruka ; May, Silvia ; Meyer, Sonja ; Morita, Satoshi ; Nakanishi, Nobuhiro ; Nawa, Kohei ; Nippoldt, Astrid ; Reihle, Boris ; Takami, Aya ; Yamada, Yasutaka ; Yamaguchi, Asuka ; Yorigami, Kuri
biog. p. 92-93
Engels
Boomerang Art Project, Part one : Omuro House, Kyoto Art Center, Kyoto, 21 - 29 October 2000 ; Part two : Künstlerhaus Bremen, Gesellschaft für Aktuelle Kunst, Bremen, 10 March - 15 April 2001
boek